Fermented black radish (Raphanus sativus L. var. niger) attenuates methionine and choline deficient diet‐induced nonalcoholic fatty liver disease in mice. Issue 10 (9th September 2019) - Ahn, Meejung; Kim, Jeongtae; Choi, Yuna; Ekanayake, Poornima; Chun, Ji‐Yeon; Yang, DaWun; Kim, Gi-Ok; Shin, Taekyun
Abstract: As one of the wide‐ranging form of chronic liver disease, there are only limited therapeutic options for nonalcoholic fatty liver disease (NAFLD). We evaluated whether fermented black radish ( Raphanus sativus L. var. niger ; FBR) ameliorates lipid accumulation, inflammation, and hepatic fibrosis, which are characteristics of the pathogenesis of NAFLD. Fermented black radish treatment reduced lipid accumulation in 3T3‐L1 adipocytes, which appeared to be associated with the downregulation of adipogenic transcription factors, including sterol regulatory element‐binding protein 1c, CCAAT/enhancer‐binding protein α, peroxisome proliferator‐activated receptor γ, and lipid accumulation‐related genes including adipocyte protein‐2 and fatty acid synthase. Administration of FBR to C57BL/6J mice challenged with methionine and choline deficient (MCD) diet significantly attenuated the increased serum levels of alanine aminotransferase, aspartate aminotransferase, alkaline phosphatase, and triglyceride. In addition, treatment with FBR interestingly repressed the hepatic inflammation induced with MCD diet, by lowering the expression of inducible nitric oxide synthase and suppressing the inactivation of macrophages and Kupffer cells in the liver. Fermented black radish was also shown to mitigate liver fibrosis through the inhibition of alpha‐smooth muscle actin, transforming growth factor beta‐1, and collagen type I alpha 1 chain. Our results indicate that FBR ameliorates NAFLD and its related metabolic disease by regulating multiple pathways, suggesting that FBR may be an effective dietary supplement for ameliorating NAFLD. Abstract : Fermented black radish to C57BL/6J mice fed a MCD diet significantly attenuated the increased serum levels. Fermented black radish treatment dramatically suppressed MCD diet‐induced hepatic steatosis, inflammation, and fibrosis